Bile salt recognition by human liver fatty acid binding protein. (18th February 2015) - Favretto, Filippo; Santambrogio, Carlo; D'Onofrio, Mariapina; Molinari, Henriette; Grandori, Rita; Assfalg, Michael
<x xml:space="preserve">Abstract</x> Fatty acid binding proteins (FABPs) act as intracellular carriers of lipid molecules, and play a role in global metabolism regulation. Liver FABP (L‐FABP) is prominent among FABPs for its wide ligand repertoire, which includes long‐chain fatty acids as well as bile acids (BAs). In this work, we performed a detailed molecular‐ and atomic‐level analysis of the interactions established by human L‐FABP with nine BAs to understand the binding specificity for this important class of cholesterol‐derived metabolites. Protein–ligand complex formation was monitored using heteronuclear NMR, steady‐state fluorescence spectroscopy, and mass spectrometry. BAs were found to interact with L‐FABP with dissociation constants in the narrow range of 0.6–7 μm; however, the diverse substitution patterns of the sterol nucleus and the presence of side‐chain conjugation resulted in complexes endowed with various degrees of conformational heterogeneity. Trihydroxylated BAs formed monomeric complexes in which single ligand molecules occupied similar internal binding sites, based on chemical‐shift perturbation data. Analysis of NMR line shapes upon progressive addition of taurocholate indicated that the binding mechanism departed from a simple binary association equilibrium, and instead involved intermediates along the binding path. The co‐linear chemical shift behavior observed for L‐FABP complexes with cholate derivatives added insight into conformational dynamics in the presence of ligands. The observed spectroscopic features of L‐FABP/BA complexes, discussed in relation to ligand chemistry, suggest possible molecular determinants of recognition, with implications regarding intracellular BA transport. Our findings suggest that human L‐FABP is a poorly selective, universal BA binder.